Extreme places : highest, hottest, largest, coldest, wettest, deepest, driest. - Atkinson, David (AA Publishing, 2011)
This is beautiful book transports you to the highest, hottest, coldest, most dramatic and most remote places on earth. Discover the icy expanse of the Baltoro Glacier in Pakistan, the bizarre and exotic wildlife of Madagascar, the searing heat of the Australian Outback and the power of the Iguassu Falls in South America.